Correlation between Progressive Adsorption of Plasminogen to Blood Clots and Their Sensitivity to Lysis - Sabovic, M; Lijnen, H R; Keber, D; Collen, D (Thrombosis and Haemostasis, 1990)
The binding of plasminogen to preformed human plasma clots immersed in citrated human plasma was measured and correlated with the sensitivity of these clots to lysis with recombinant tissuetype plasminogen activator (rt-PA), recombinant single-chain urokinase-type plasminogen activator (rscu-PA) or two chain urokinase-type plasminogen activator (tcu-PA, urokinase)When 0.15 ml plasma clots were compressed mechanically to about 1% of their original weight, and immersed in 0.15 ml plasma, 131I-labeled native plasminogen (Glu-plasminogen) adsorbed progressively from the plasma milieu onto the clot; binding was 3 ± l% (, - 10) after 1 h, 7 ± L% after 12h and 12 ± l% after 48 h. This was associated with an increased sensitivity of the clot to lysis; 50% clot lysis in 4 h was obtained with 65 ± 5 ng/ml (n= 3) rt-PA before and 30 ± 5 ng/ml (n = 3) after 48 h preincubation in plasma (p <p 0.01), with corresponding values of 660 ± 55 ng/ml (n = 3) and 280 125 ng/ml (n = 3) for rscu-PA, (p < 0.01), ind 800 ± 85 nglml (n = 3) and 270 ± 35 ngt ml (n = 3) for urokinase (p < 0.01). Additional binding of plasminogen and increased sensitivity to lysis were reduced or abolished when the clot was preincubated in plasminogendepteted or in t-PA-depleted plasma, of when 20 mM 6-aminohexanoic acid or 2,000 KIU/ml aprotinin were added. When 0.1- ml retracted whole blood clots were preincubated in 1- ml plasma, 50% clot lysis in 4h was obtained with 1,150 ± L60 ng/ml (n = 3) rt-PA before incubation and 55 ± 10 ng/ml (n = 3) after 48 h preincubation (p < 0.01), with corresponding values of 3,200 ± 430 ng/ml (n = 3) and 190 ± 30 ng/ml (n = 3) for rscu-PA (p < p0.01), and > 1,600 ng/ml and 220 ± 2A ng/ml (n = 3) for urokinase.These results show that preincubation of compressed plasma clots or retracted whole blood clots in plasma causes a progressive increase in both the binding of plasminogen and the sensitivity to lysis with plasminogen activators. Increased plasminogen binding may be the result of partial fibrindigestion.